Percutaneous Interventions for Structural Heart Disease : An Illustrated Guide - Reimers, Bernhard; Moussa, Issam; Pacchioni, Andrea (Springer International Publishing : Imprint: Springer, 2017)
This book presents the percutaneous techniques and technologies most frequently employed in structural interventional cardiology, focusing especially on how to optimize outcomes and minimize risk. Interventional procedures for aortic stenosis, mitral regurgitation, left atrial appendage closure, patent foramen ovale closure, and closure of interatrial and interventricular defects are clearly presented step by step with the aid of a wealth of images. These descriptions are complemented by a case-based analysis of the various structural pathologies and their complications. Clear guidance is also provided on patient selection, preoperative evaluation, and choice of available devices. The authors are all acknowledged experts with extensive experience in laboratories and surgical units. The book fully reflects the rapid changes in structural interventional cardiology that have occurred during recent years. These advances are in particular due to the introduction of transcatheter aortic valve implantation, which allows cardiac surgeons to achieve excellent outcomes in patients at high surgical risk. Other exciting developments include new technologies that permit better treatment of other structural cardiac pathologies and valid alternatives to medical therapy in particular patient groups.
Keywords: Medicine.; Cardiology.; Cardiac surgery.; elektronické knihy; electronic books